Assessment of the efficacy and efficiency of rapid rehydration in children with dehydration due to gastroenteritis in the rehydration unit of Red Cross War Memorial Children's Hospital - Webb, Nicholas Guy (Division of Paediatric Medicine, 2018)
Background: Dehydration due to acute gastroenteritis (AGE) remains a leading cause of child death worldwide. The primary treatment is enteral rehydration. Children who fail a trial of oral fluids require rehydration in hospital, preferably via nasogastric tube. Traditionally, children have been rehydrated over 24 hours; 'Standard Rehydration' (SR). Most treatment guidelines now recommend 'Rapid Rehydration' (RR) over 4-6 hours. There are limited data comparing RR to SR, especially from low-resource settings. Objectives: To assess the efficacy and efficiency of RR in children with AGE in the Rehydration Unit of Red Cross War Memorial Children's Hospital, Cape Town. Methods: A retrospective cohort study was performed. The intervention cohort contained 67 children who received RR in March 2007. The control cohort contained 76 children who received SR in March 2006. The outcome measures were weight and hydration status at 4 hours and time to maximum weight to measure efficacy; and length of hospital stay (LOS) to measure efficiency. Results: Children in the intervention cohort experienced greater weight gain (p<0.01) and lower dehydration scores (p=0.01) at 4 hours. There was no difference in time to maximum weight. The LOS for the two groups were not statistically different. Conclusion: RR is an effective method of rehydrating children with AGE. In contrast to two studies in well-developed settings, reduction in LOS following RR could not be demonstrated. There is no reason not to adopt RR as the predominant rehydration method in settings such as ours. More research is required to evaluate the efficiency of RR.